S-RNase Alleles Associated With Self-Compatibility in the Tomato Clade: Structure, Origins, and Expression Plasticity - Broz, Amanda K.; Miller, Christopher M.; Baek, You Soon; Tovar-Méndez, Alejandro; Acosta-Quezada, Pablo Geovanny; Riofrío-Cuenca, Tanya Elizabet; Rusch, Douglas B.; Bedinger, Patricia A. (Frontiers in Genetics, 2021)
The self-incompatibility (SI) system in the Solanaceae is comprised of cytotoxic pistil S-RNases which are countered by S-locus F-box (SLF) resistance factors found in pollen. Under this barrier-resistance architecture, mating system transitions from SI to self-compatibility (SC) typically result from loss-of-function mutations in genes encoding pistil SI factors such as S-RNase. However, the nature of these mutations is often not well characterized. Here we use a combination of S-RNase sequence analysis, transcript profiling, protein expression and reproductive phenotyping to better understand different mechanisms that result in loss of S-RNase function. Our analysis focuses on 12 S-RNase alleles identified in SC populations and species across the tomato clade. In six cases, the reason for gene dysfunction due to mutations is evident. The six other alleles potentially encode functional S-RNase proteins but are typically transcriptionally silenced. We identified three S-RNase alleles which are transcriptionally silenced under some conditions but actively expressed in others. In one case, expression of the S-RNase is associated with SI. In another case, S-RNase expression does not lead to SI, but instead confers a reproductive barrier against pollen tubes from other tomato species. In the third case, expression of S-RNase does not affect self, interspecific or inter-population reproductive barriers. Our results indicate that S-RNase expression is more dynamic than previously thought, and that changes in expression can impact different reproductive barriers within or between natural populations.